Peran Lembaga Dakwah Kampus Dalam Membina Akhlak Pada Mahasiswa STAI Ibnu Rusyd Kotabumi Lampung Utara - Hidayah, Wahyudi; Mutiara, Yolanda; Hidayah, Ridho (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
The purpose of this study was to determine the concept of morality and efforts to foster morality of Ibnu Rusyd Islamic Boarding School students. Based on field data using qualitative methods. The data collected were obtained through observation, in-depth interviews and documentation studies, while the analysis used qualitative descriptive analysis techniques, namely descriptions and descriptions of data collected in full about a real situation. The results of this study indicate that the Ibnu Rusyd Islamic Boarding School campus dakwah institution has a concept of morality and makes efforts to foster and direct. The concept of moral development and efforts to foster morality are two things that are closely related. In the concept of improving morality, LDK has 4 organized systems, namely (1) Preparing and improving individual abilities to do good deeds, (2) Preparing and improving participant skills to do good deeds at the dakwah movement level, (3) Preparing and improving participant skills to do good deeds at the community level, (4) Preparing and improving participant skills to do good deeds and interact with non-Muslims. In line with the efforts that have been set by LDK in the form of a work program that includes three aspects, namely the spiritual aspect, the fikriyah/intellectual aspect, and the physical aspect (physical endurance) as well as the muamalah/relationship aspect with fellow human beings. In terms of organization, LDK tends to be open (inclusive) but as a movement it tends to be exclusive. This can be seen from several things, namely the identity of the typical appearance of LDK cadres (wearing wide headscarves, Palestinian flags, not shaking hands with the opposite sex) then the use of headscarves (dividers) in activities to provide distance in interacting with students outside the LDK UKM.